Urinary cytokines correlate with acute kidney injury in critically ill COVID-19 patients. (October 2021) - Gradin, A.; Andersson, H.; Luther, T.; Anderberg, S. Bülow; Rubertsson, S.; Lipcsey, M.; Åberg, M.; Larsson, A.; Frithiof, R.; Hultström, M.
Abstract: Background: Acute kidney injury is common in COVID-19 patients admitted to the ICU. Urinary biomarkers are a non-invasive way of assaying renal damage, and so far, urinary cytokines are not fully investigated. The current study aimed to assess urinary cytokine levels in COVID-19 patients. Methods: Urine was collected from COVID-19 patients (n = 29) in intensive care and compared to a preoperative group of patients (n = 9) with no critical illness. 92 urinary cytokines were analyzed in multiplex using the Olink Target 96 inflammation panel and compared to clinical characteristics, and urinary markers of kidney injury. Results: There were strong correlations between proinflammatory cytokines and between urinary cytokines and urinary kidney injury markers in 29 COVID-19 patients. Several cytokines were correlated to kidney injury, 31 cytokines to AKI stage and 19 cytokines correlated to maximal creatinine. Conclusions: Urinary inflammatory cytokines from a wide range of immune cell lineages were significantly upregulated during COVID-19 and the upregulation correlated with acute kidney injury as well as urinary markers of kidney tissue damage.